Ethical and legal concepts: confidentiality. (2nd January 2022) - Ellis, Peter; Ellis, Hannah
Abstract : Peter Ellis and Hannah Ellis explore the definition of confidentiality and why it needs to be protected in a kidney care setting but cannot always be maintained